Reviewing Regulations on Rights of Persons with Disabilities in Vietnam to Advance the Implementation of the Convention on the Rights of People with Disabilities - Le Dinh Nghi (Jambe Law Journal, 2022)
Viet Nam signed the International Convention on the Rights of Persons with Disabilities in 2007 and ratified it in 2014, recognizing all of the rights of PWDs included in the Convention without reservation. In addition, as a result of member states’ commitment, policies and legislation related to PWDs have been adjusted in order to adapt to socioeconomic developments in order to guarantee that PWDs can completely participate fully in society. However, there are relevant legal gaps between the 2010 Law on Persons with Disabilities and the International Convention on the Rights of Persons with Disabilities, particularly, in terms of obstacles, problems, and challenges in implementing rights to education, health care, and vocational training. Through analyzing the barriers, challenges, and legal gaps compared to the International Convention on the Rights of Persons with Disabilities, the article proposes some recommendations to ensure that Viet Nam fully implements its commitments under the Convention.